2002
DOI: 10.1645/0022-3395(2002)088[0621:roacct]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Acanthamoeba castellanii Cysts to Physical, Chemical, and Radiological Conditions

Abstract: Resistance of Acanthamoeba castellanii cysts to disinfection agents, antimicrobial agents, heat, freeze-thawing, ultraviolet radiation (UV), gamma irradiation, and cellulase were evaluated in vitro. Following exposure to different agents, the cysts were removed and cultured for A. castellanii trophozoites for 3-14 days. Solutions containing 20% isopropyl alcohol or 10% formalin effectively killed A. castellanii cysts. Hydrogen peroxide (3%, AOSept Disinfectant) effectively killed A. castellanii cysts after 4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(58 citation statements)
references
References 17 publications
0
55
0
3
Order By: Relevance
“…Free-living protozoa on dishcloths are frequently exposed to stress conditions such as desiccation, disinfection and cleaning treatments. Through cyst formation, various protozoan species can survive unfavorable conditions (Aksozek et al, 2002;Coulon et al, 2010;Dupuy et al, 2014;Sriram et al, 2008) which may also be the case on dishcloths.…”
Section: Discussionmentioning
confidence: 99%
“…Free-living protozoa on dishcloths are frequently exposed to stress conditions such as desiccation, disinfection and cleaning treatments. Through cyst formation, various protozoan species can survive unfavorable conditions (Aksozek et al, 2002;Coulon et al, 2010;Dupuy et al, 2014;Sriram et al, 2008) which may also be the case on dishcloths.…”
Section: Discussionmentioning
confidence: 99%
“…It exists in active trophozoite form but can also encyst, creating the potential for reactivation of disease after treatment is ended. 160 Several studies have concluded that infection with Acanthamoeba does not protect against reinfection, suggesting that immunological defence is predominantly mediated by the innate immune system. [161][162][163][164] Patients presenting with Acanthamoeba infection have been found to have low levels of anti-Acanthamoeba sIgA in their tearfilms, 165 raising the suggestion that IgA is an important protective factor against infection at the corneal surface.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…Améby tvoria perzistentné cysty, ktoré pomáhajú bakté-riám prekonávať extrémne teploty, vyschnutie, vystavenie ultrafialovému žiareniu (23). Navyše tieto cysty poskytujú ochranu pred niektorými chemikáliami použí-vanými pri úprave vody, ako je chlór (24) a trochu menej monochloramín (25).…”
Section: Prežívanie a Množenie Rôznych Baktérií V Amébachunclassified